Cytokines and Angiogenesis in the Corpus Luteum - António M. Galvão; Graça Ferreira-Dias; Dariusz J. Skarzynski (Mediators of Inflammation)
In adults, physiological angiogenesis is a rare event, with few exceptions as the vasculogenesis needed for tissue growth and function in female reproductive organs. Particularly in the corpus luteum (CL), regulation of angiogenic process seems to be tightly controlled by opposite actions resultant from the balance between pro- and antiangiogenic factors. It is the extremely rapid sequence of events that determines the dramatic changes on vascular and nonvascular structures, qualifying the CL as a great model for angiogenesis studies. Using the mare CL as a model, reports on locally produced cytokines, such as tumor necrosis factor α (TNF), interferon gamma (IFNG), or Fas ligand (FASL), pointed out their role on angiogenic activity modulation throughout the luteal phase. Thus, the main purpose of this review is to highlight the interaction between immune, endothelial, and luteal steroidogenic cells, regarding vascular dynamics/changes during establishment and regression of the equine CL.